Monolateral cystic acne on residua of hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
This 3-month-old child (Fig. 1), who at birth had a diagnosis of port-wine stain, has in fact a large hemangioma on the right hemiface. Imaging techniques, made after the report of PHACE syndrome, excluded its complications. At 10 years (Fig. 2) persist telangiectasias and widening of the right eyebrow with thin hairs. At 16 years (Fig. 3, 4) is present cystic acne only on the right hemiface, likely expression of the role of residual vasodilation as a localization and severity factor of acne.